(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2022)
The reader of this note will find a series of short arguments that summarize the characteristics which I consider essential to a philologist’s work. The range of typologies and methods of philological approach to literary texts in the vernacular is so wide that its boundaries cannot be easily defined. Moreover, in philology, each case is a case in and of itself that is to be dealt with and solved in specific and particular ways each time; nothing or almost nothing can be generalized.